Menggali Warisan Hannah Arendt dalam “Asal-Usul Totalitarisme” - Alois A. Nugroho (Respons: Jurnal Etika Sosial, 2009)
Abstract: Arendt’s analysis of totalitarism in The Origins of Totalitarism has combined several dimensions of power: imperialism, racism, and anti-Semitism. Under these exercises of power, polis as a model of politics is reduced into the holocaust and colonization. This article finds out that those processes bring forth the society into the dichotomy between the pariah and the parvenu, the people and the mass, human qua human and human qua citizen, and the authentic and the unauthentic. This phenomenological analysis of the dichotomy shows that emotion may be the only sources of disturbancesKata Kunci: Totalitarisme, rasisme, pariah, pervenu, massa, warga negara, yang otentik